MAML2 rearrangement in primary pulmonary mucoepidermoid carcinoma and the correlation with FLT1 expression. - Fen Zhu; Weige Wang; Yingyong Hou; Jindong Shi; Zilong Liu; Deming He; Chunxue Bai; Shanqun Li; Liyan Jiang (PLoS ONE)
Introduction Primary pulmonary mucoepidermoid carcinoma (PMEC) is an uncommon neoplasm with remarkable resemblance to mucoepidermoid carcinoma of the salivary glands. The latter has been shown to harbor t(11,19) resulting in MECT1-MAML2 fusion, which may be of diagnostic and prognostic values. However, the importance of such feature in PMEC has not been well studied. Methods We detected MAML2 rearrangement using fluorescence in situ hybridization (FISH) in tissue samples from 42 cases of PMEC and 40 of adenosquamous carcinoma (ASC), and the expression of potential downstream targets of MECT1-MAML2, including HES1, FLT1 and NR4A2 with immunohistochemistry (IHC). The findings were then examined regarding the clinicopathological parameters and patient outcomes. Results FISH analysis revealed MAML2 rearrangement in 50% of the PMEC cases, and such property was prominent in considerable younger patients (33 versus 60 years; p = 0.001) and restricted to cases of low and intermediate grades. IHC analysis showed that FLT1 and HES1 were expressed at lower level in MAML2 rearranged group than MAML2 non-rearranged group (p<0.001 and p = 0.023, respectively). Survival analysis showed significant correlation between MAML2 rearrangement and overall survival (p = 0.023) or disease-free survival (p = 0.027) as well as correlation between FLT1 and overall survival (p = 0.009). Conclusions MAML2 rearrangement appears frequent in PMEC and specific with this tumor. Both the presence of MAML2 rearrangement and absence of FLT1 tend to confer a favorable clinical outcome. These findings suggest that molecular detection of MAML2 rearrangement combined with FLT1 may be of important clinical value for PMEC.